(3eSGdc GdeHJOi heTGHc GdebJOis ((3YeQ Hf YHO GdeMSf Hf Ydi Hf CHh HcQ GdHUQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi chf GdcGFfGJ HbOQJg hHYO adeG HQR GdCeQ ef GdLfGH GdcQje GdYGdi GdCaVdi HCf CLeY dg cJGHkG ef SGFQ GdYdhe GdMcejI hZjQ Pdc hSejJg eSGdc GdeHJOF heTGHc GdebJOi GdHGH GdChd ai GdfMh s
(3BNQgG (B:s
(3aEf RGOJ GdfGQ Ydi GdcHQjJ ai Chd djdI ef Pdc GdbGdH GdcHQjJ hRHOg Ydi GdhUa hGSJaWQg Edi Cf jMUd caGjfc Je GdcJGH HMeO Gddg hMSf Jhajbg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeYGQa GdYGeIs